Shear wave velocity structure in the middle segment of the Xiaojiang fault zone using ambient noise tomography - Liang, Yao; Xie, Tongtong; Lu, Zhanwu; Li, Qiusheng; Zhang, Xinyan; Wang, Guangwen; Wang, Guan; Chen, Si; Chang, Chang (Frontiers in Earth Science, 2023)
The middle segment of the Xiaojiang fault zone consists of strike-slip faults with frequent strong and medium–strong earthquakes under the joint influence of NE-trending faults and deep structural characteristics. The distribution characteristics of the deep subfaults of each branch need to be revealed. Two short-period dense array survey lines are deployed in the area. Shear wave velocity structures are obtained using ambient noise tomography. The results reveal that the faults in each branch dip nearly eastward, with strike-slip characteristics in the north‒south direction. Strong velocity lateral variation infer imply that the deformation characteristics of the upper crust may be brittle. NE faults are observed, which are characterized by typical compression. The high-velocity zone in the Songming Basin may be related to the deeper upwelling of high-velocity strata in the upper crustal flow.